2007
DOI: 10.1681/asn.2006121417
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Changes after Exposure to Sterile Solutions by Catheter

Abstract: Most current animal models that are used to study effects of long-term peritoneal exposure to dialysis solutions use an indwelling catheter for daily injections. It was hypothesized that the presence of a foreign body in the peritoneal cavity (PC) might alter the inflammatory response to the solutions and that the response would depend on exposure duration. For addressing these, long-term injections were carried out for 2 to 8 wk in 90 Sprague-Dawley rats: 40 via a subcutaneous port connected to a silicone cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 23 publications
3
52
4
Order By: Relevance
“…infiltration compared with the N group, which was slightly different from Flessner's study [47]. Meanwhile, the HG group showed a pronounced thicker peritoneum and more inflammatory response than the NS group.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…infiltration compared with the N group, which was slightly different from Flessner's study [47]. Meanwhile, the HG group showed a pronounced thicker peritoneum and more inflammatory response than the NS group.…”
Section: Discussioncontrasting
confidence: 83%
“…There are two basic types of PD models in nonuremic rats: one that are treated with daily intraperitoneal injection of PD solution [22,25,45] and another that are infused with PD solution after implantation of biomaterials like silicone or Dacrone [9,44,46]. It has been demonstrated that intraperitoneal implantation of silicone catheter may induce inflammatory response and important mesothelial changes on peritoneum [47][48][49]. In our in vivo result, the NS group inserted with a silicone catheter showed a mildly increased peritoneum thickness but no obvious inflammatory cell proliferation and The group NS showed a mildly higher protein and mRNA expression of a-SMA and TGF-b1 than the group NC; The group L-RAPA and group H-RAPA both significantly decreased the protein and mRNA expression of a-SMA and TGF-b1, which were significantly increased in the group HG.…”
Section: Discussionmentioning
confidence: 99%
“…Patients on PD have many predisposing factors for chronic intraperitoneal inflammatory conditions; therefore, these patients likely have increased risk for adhesion compared with the general population. Repeated exposures to bio-incompatible PD solutions are related to the development of intraperitoneal inflammation [12], and the PD catheter itself is also independently associated with the disruption of peritoneal membrane integrity, which contributes to intraperitoneal adhesion [13]. However, anatomical adhesion band in this case was not confirmed.…”
Section: Discussionmentioning
confidence: 81%
“…In rat models of PD, the catheter implant appeared to make a large contribution to the damage of the parietal peritoneum. Changes in peritoneal structure, histology, and function were more profound when PD fluids were instilled through a catheter implant compared with intraperitoneal (IP) injections with a needle (12,13). These studies emphasize that the effects of dialysis solutions on peritoneal pathology, function, and inflammatory responses in animal models cannot be examined without careful differentiation of the effects of the PD fluid versus the peritoneal catheter.…”
Section: P Eritonitis Is a Major Problem In Peritoneal Dialysis (Pd)mentioning
confidence: 99%